Lhx2 regulates bone remodeling in mice by modulating RANKL signaling in osteoclasts - Kim, J H (Nature Publishing Group, 2014)
The LIM homeobox 2 (Lhx2) transcription factor Lhx2 has a variety of functions, including neural induction, morphogenesis, and hematopoiesis. Here we show the involvement of Lhx2 in osteoclast differentiation. Lhx2 was strongly expressed in osteoclast precursor cells but its expression was significantly reduced during receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclastogenesis. Overexpression of Lhx2 in bone marrow-derived monocyte/macrophage lineage cells (BMMs), which are osteoclast precursor cells, attenuated RANKL-induced osteoclast differentiation by inhibiting the induction of nuclear factor of activated T cells c1 (NFATc1). Interestingly, interaction of Lhx2 proteins with c-Fos attenuated the DNA-binding ability of c-Fos and thereby inhibited the transactivation of NFATc1. Furthermore, Lhx2 conditional knockout mice exhibited an osteoporotic bone phenotype, which was related with increased osteoclast formation in vivo. Taken together, our results suggest that Lhx2 acts as a negative regulator of osteoclast formation in vitro and in vivo. The anti-osteoclastogenic effect of Lhx2 may be useful for developing a therapeutic strategy for bone disease.